2020
DOI: 10.3390/ijerph17217805
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exogenous Lactate Administration on the IGF1/Akt/mTOR Pathway in Rat Skeletal Muscle

Abstract: We investigated the effects of oral lactate administration on protein synthesis and degradation factors in rats over 2 h after intake. Seven-week-old male Sprague–Dawley rats were randomly divided into four groups (n = 8/group); their blood plasma levels of lactate, glucose, insulin, and insulin-like growth factor 1 (IGF1) were examined following sacrifice at 0, 30, 60, or 120 min after sodium lactate (2 g/kg) administration. We measured the mRNA expression levels of protein synthesis-related genes (IGF recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…Interestingly, we have previously confirmed the potential of lactate as a supplement by examining the effects of lactate intake at rest on metabolism [ 23 , 24 ]. The main aim of the present study was to investigate the effect of lactate intake on metabolism during exercise.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Interestingly, we have previously confirmed the potential of lactate as a supplement by examining the effects of lactate intake at rest on metabolism [ 23 , 24 ]. The main aim of the present study was to investigate the effect of lactate intake on metabolism during exercise.…”
Section: Discussionmentioning
confidence: 89%
“…Mice were randomly divided into the EX and EXLA groups ( n = 8 per group, average weight: EX group = 32.4 ± 0.84, EXLA group = 32.5 ± 1.28). Prior to conducting the experiment, all groups were fasted for 8 h. The EXLA group was administered 3 g/kg of sodium lactate with an oral sonde and the EX group an equal amount of a saline solution [ 23 , 41 ]. The mice were orally administered the appropriate supplement 30 min before a moderate intensity (about 60–70% VO 2max ) exercise was conducted for 30 min (treadmill exercise at a speed of 18 m/min and slope of 6°) [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…## P < 0.01 compared to H/R-exo. ^^P < 0.01 compared to (H/R + NC inhibitor)-exo in some diseases [30][31][32]. Previous research found that IGF1 overexpression may promote the migration of trophoblast cells [24].…”
Section: Discussionmentioning
confidence: 91%
“…This process is necessary for maintaining the cellular functions, which in turn protect the organisms against inflammatory injuries ( 21 , 22 ). Recent reports have revealed that autophagy can inhibit the formation of HSs ( 23 25 ). These findings indicated that autophagy serves a crucial role during the formation of HS; however, the relationship between FAM225B and cell autophagy is yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%